Dairy of a wimpy kid Hard luck - Kinney, Jeff (London: Penguin, 2015)
Greg Heffleys on a losing streak His best friend Rowley Jefferson has ditched him and finding new friends in middle school is proving to be a tough task To change his fortunes Greg decides to take a leap of faith and turn his decisions over to chance Will a roll of the dice turn things around or is Gregs life destined to be just another hardluck story Perfect for readers of 8 and also reluctant readers You can also discover Greg on the big screen in any one of the three Wimpy Kid Movie boxoffice smashes. About the Author Jeff Kinney is a #1 New York Times bestselling author and a five-time Nickelodeon Kids' Choice Award winner for Favorite Book. Jeff has been named one of Time magazine's 100 Most Influential People in the World. He is also the creator of Poptropica, which was named one of Time magazine's 50 Best Websites. He spent his childhood in the Washington, D.C., area and moved to New England in 1995. Jeff lives with his wife and two sons in Massachusetts, where they own a bookstore, An Unlikely Story.
WHAT'S IN DIARY OF A WIMPY KID? 50% words, 50% cartoons, 100% hilarious! Stories that all readers can't wait to get their hands on Laughter guaranteed!